Secure Multiparty Computations for Collaboration between Competing Service Providers - David H. Danoyan (Изд-во НАН РА)
We introduce a platform for secure computations and escribe the platform workflow. We detail the Golreich-Micalli-Widgerson protocol employed for secure multiparty computation in our platform with optimization techniques applied to it. Being based on white-box cryptography, the underlying oblivious transfer protocol avoids the use of expensive public key operations and provides good overhead compared to similar systems. Also we point out some useful application scenarios and provide a real world application design based on our platform.
Keywords: Mathematics; Computer software